Bladder dysfunction in Duchenne muscular dystrophy. Issue 4 (1st April 2003) - MacLeod, M; Kelly, R; Robb, S A; Borzyskowski, M
Abstract : Although bladder function is thought to be unaffected in Duchenne muscular dystrophy, 46/88 boys interviewed had urinary problems. Nine underwent video urodynamics, showing in eight a small capacity, hyperreflexic bladder, and in the ninth (post spinal surgery) hyperreflexia and detrusor sphincter dyssynergia. Urinary dysfunction is a treatable feature of DMD.